MATLAB Programming for Engineers, 6th Edition - Stephen J. Chapman (Cengage Learning, 2019)
Present MATLAB® as a technical programming language while emphasizing problem-solving skills with the 6th Edition of Chapman's highly successful MATLAB® PROGRAMMING FOR ENGINEERS. Students learn how to write clean, efficient and well-documented programs, while gaining an understanding of the many practical functions of MATLAB®. This edition reflects the latest advancements in MATLAB® R2018a and includes new MATLAB® GUI Apps. The first nine chapters can serve as a complete text and resource for first-year engineering students' introduction to programming and problem-solving course. The remaining chapters cover more advanced topics, such as I/O, object-oriented programming, and Graphical User Interfaces, and offer an ideal resource for a longer course. These chapter also provide an ongoing, trusted reference tool for upper-level engineering students or practicing engineers who rely upon MATLAB®.